System Monitoring and Controlling Agricultural Activities with Arduino-Based Internet of Things - Muhammad Syahril Ramadhani; Eko Junirianto; Eny Maria (TEPIAN, 2022)
Agriculture is one of the most important economic sectors in Indonesia.aHowever, the Center for IndonesianaPolicy Studies (CIPS) estimates that agricultural production will decline by 1.64% to 6.2% due to supply chain disruptions affected by the Corona pandemic. But on the other hand, during the corona pandemic as it is today, the information technology sector, mainly digital, which requires internet access, has experienced a rapid increase. In this modern era, an innovation that utilizes the latest technology is needed to create an innovation that can increase the potential of the plantation sector towards industry 4.0. Therefore, a will be developed in this research Arduino-based Internet of Things monitoring and control system can provide information about soil pH, soil moisture, air humidity, air temperature, and wind speed from plants in real-time, and control water pumps for watering. The Arduino technology can make it easier for farmers to control the conditions in plants so plants can grow and develop optimally.